1999
DOI: 10.2527/1999.773630x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of stearoyl coenzyme A desaturase gene expression and adiposity in bovine subcutaneous adipose tissue.

Abstract: This investigation addressed the hypothesis that stearoyl coenzyme A desaturase (SCD) gene expression would serve as a postnatal marker of adipocyte differentiation in bovine s.c. adipose tissue. Samples of tailhead s.c. adipose tissue were obtained by biopsy from preweaning steer calves 2.5 wk, 5 mo, and 7.5 mo of age and from yearling steers 12 mo of age. Samples also were obtained at slaughter when the steers were 18 mo of age. The steers sampled as yearlings were fed native pasture from weaning until 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 22 publications
5
53
0
Order By: Relevance
“…Similarly, Lee et al (2005) observed peak SCD mRNA at 12 months of age in muscle from Hanwoo steers. The rate of de novo fatty acid biosynthesis increased gradually in the adipose tissue of Angus steers, but lagged behind the elevation in desaturase gene expression (Martin et al 1999). These data suggest that desaturase activity is essential for the subsequent development of lipogenic capacity of subcutaneous adipose tissue in growing steers.…”
Section: Figurementioning
confidence: 76%
See 3 more Smart Citations
“…Similarly, Lee et al (2005) observed peak SCD mRNA at 12 months of age in muscle from Hanwoo steers. The rate of de novo fatty acid biosynthesis increased gradually in the adipose tissue of Angus steers, but lagged behind the elevation in desaturase gene expression (Martin et al 1999). These data suggest that desaturase activity is essential for the subsequent development of lipogenic capacity of subcutaneous adipose tissue in growing steers.…”
Section: Figurementioning
confidence: 76%
“…Expression of the ∆ 9 desaturase gene increased profoundly between weaning and 12 months of age in subcutaneous adipose tissue of Angus steers (Martin et al 1999;Fig. 6).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of CLA into lipids in ruminant tissues or in milk results, for a low part, from bacterial biohydrogenation and trans isomerisation of dietary polyunsaturated fatty acids (PUFA) (mainly linoleic acid from forages, cereals or oleaginous seeds) in the rumen [7] and, for a large part, from endogenous synthesis [8]. Synthesis of CLA can take place in the tissues of ruminants where the ∆9 desaturase enzyme is expressed i.e., the mammary gland in lactating ruminants and adipose tissues in growing ruminants [9,10]. Likewise, it has been demonstrated that vaccenic acid (another intermediate of bacterial biohydrogenation of PUFA, trans-11 C18:1) is desaturated to CLA in the mammary gland of lactating cows, and has been estimated to represent about 60 to 90% of CLA deposited in milk fat [8,11,12], whereas no desaturation of VA into CLA occurred in the liver of ruminants [13].…”
Section: Introductionmentioning
confidence: 99%